Multidimensional Well-Being at the Top: Evidence for Germany - Andreas Peichl; Nico Pestel (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper employs a multidimensional approach for the measurement of well-being at the top of the distribution using German SOEP micro data. Besides income as traditional indicator for material well-being, we include health as a proxy for nonmaterial quality of life as well as self-reported satisfaction with life as dimensions. We find that one third of the German population is well-off in at least one dimension but only one percent in all three dimensions simultaneously. While the distribution of income has become more concentrated at the top, the concentration at the top of the multidimensional well-being distribution has decreased over time. Moreover, health as well as life satisfaction contribute quite substantially to multidimensional wellbeing at the top which has important policy implications.
Keywords: D31; D63; I31; 330; Multidimensional measurement; well-being; Germany; Vermögen; Lebensqualität; Zufriedenheit; Gesundheit; Deutschland